2015 31st IEEE International Conference on Data Engineering Workshops 2015
DOI: 10.1109/icdew.2015.7129564
|View full text |Cite
|
Sign up to set email alerts
|

Hotel recommendation based on user preference analysis

Abstract: Recommender system offers personalized suggestions by analyzing user preference. However, the performance falls sharply when it encounters sparse data, especially meets a cold start user. Hotel is such kind of goods that suffers a lot from sparsity issue due to extremely low rating frequency. In order to handle these issues, this paper proposes a novel hotel recommendation framework. The main contribution includes: 1) We combine collaboration filtering (CF) with content-based (CBF) method to overcome sparsity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…According to Zhang et al [9] Collaborative Filtering (CF) based approach is very successful technology in all RSs. The [10], [11] has reported that there are three fundamental challenges faced by CF approaches such as − Cold start challenge rise where an item appears which has not been rated before, recommendations cannot be made for it or when a new user without any prerecorded profile appears [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Zhang et al [9] Collaborative Filtering (CF) based approach is very successful technology in all RSs. The [10], [11] has reported that there are three fundamental challenges faced by CF approaches such as − Cold start challenge rise where an item appears which has not been rated before, recommendations cannot be made for it or when a new user without any prerecorded profile appears [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…− Sparsity challenge appears when there are numerous items but too less rating values are available in the initial stage of recommendation [10], [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies use only a comprehensive score, which results in a serious loss of information [14,15]. In recent years, with the development of text analysis technology, several researches have combined ratings and online reviews to select items [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al combine collaborative filtering with content-based method to overcome the sparsity issue from low rating frequency problem [1]. Fumiyo Fukumoto et al incorporate different aspects of a hotel into account for a hotel recommendation model.…”
Section: Related Workmentioning
confidence: 99%
“…Hotel review mining has been studied by many researchers [1][2][3]. Zhang et al combine collaborative filtering with content-based method to overcome the sparsity issue from low rating frequency problem [1].…”
Section: Related Workmentioning
confidence: 99%